FAKTOR-FAKTOR YANG MEMPENGARUHI BID-ASK SPREAD PADA PERUSAHAAN MANUFAKTUR - Adistie Nucke Arista Dewi; Indri Kartika (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2015)
The amount of information asymmetry faced by dealers will be reflected in the spread. Dealers will try to maintain the bid-ask spreads are optimal, so the need to determine the factors that affect the bid- ask spread . This study aimed to analyze the effect of stock returns, trading volume, variants of stock returns and stock prices to bid-ask spread stock . The population in this study are manufacturing companies that publish financial statements in the period 2010-2012 . The samples with purposive sampling, to obtain the 61 companies . From the data obtained were processed and analyzed using SPSS 19 o’clock, by means of multiple linear regression analysis. Multiple linear regression analysis was preceded with the classical assumption. The results showed that the first, the stock return significant negative effect on the bid- ask spread stock. Second, the volume of stock trading is not a significant positive effect on the bid- ask spread stock . Third, the stock price significant negative effect on the bid- ask spread stock. Fourth, variant stock returns are not significant positive effect terdahap stock bid-ask spread. Future studies could add other variables that stock price fluctuations (volatility) in the given period. Predicted volatility can affect the bid- ask spread stocks as investors memilliki enough information about the investment that not only perform certain transactions on the stock .